COMBINED ANESTHESIA IN PULMONARY RESECTION - M. M. Orlov; E. V. Nedashkovskiy; A. E. Rakhov; E. A. Malyshkin; N. V. Maltseva (Вестник анестезиологии и реаниматологии)
In order to improve outcomes of surgical treatment of thoracic diseases, the peri-operative protection is to be constantly enhanced. Goal: to assess the effect of combined anesthesia with thoracic epidural analgesia in the peri-operative period on hemodynamics and respiratory exchange during radical pulmonary surgery. Subjects and methods. The prospective randomized study was performed aiming to assess the effect of various options of anesthesia in 46 patients who had planned radical pulmonary surgery. The patients were randomly divided into two groups. Group 1 (n = 23) had combined anesthesia. Analgesia was provided through segmental epidural block on the level of Th4 ‒Th5 by intermittent bolus dosing of 0.75% solution of ropivacaine (0.7-0.8 mg/kg) and fentanyl (1.3-1.5 mcg/kg), and during the surgery, the mixture of 0.02% solution of ropivacaine and fentanyl (4 mcg/kg) was continuously infused at the rate of 4-6 ml/h. In Group 2 (n = 23), analgesia was provided by infusions of fentanyl, epidural analgesia was used in the post-operative period as a component of multi-modal post-operative pain relief. In both groups, the cortical component was provided by the low-flow inhalation of sevoflurane under BIS monitoring. Pipecuronium bromide solution was intermittently administered in order to provide muscle relaxation. Conclusion. The positive impact on hemodynamics and respiratory exchange was observed when using combined anesthesia based on thoracic epidural analgesia and inhalation anesthesia with sevoflurane.